PERAN PEMERINTAH DESA DALAM PENGEMBANGAN DAN PEMBERDAYAAN MASYARAKAT MELALUI DESA WISATA (STUDI DI DESA JURUG KABUPATEN PONOROGO) - Moch Yusuf Syaifudin; Muhammad Farid Ma'ruf (Publika, 2022)
Community empowerment is an option for the Village Government to deal with problems that exist in the Village. Whether it's economic, social, or cultural issues, community empowerment is a way to find solutions to these problems. With community empowerment, of course, both the village government and the community want an improvement in the standard of living of the people in the village. One of the problems in the village is the lack of community participation in programs from the village government. The quality of human resources in the village that are less competent will certainly affect the progress of development in the village. This study aims to analyze the role of the Jurug Village Government in community development and empowerment through the Jurug Tourism Village program. The Tourism Village Program is useful for developing the potential of Jurug Village to be able to attract tourists both inside and outside the village. Researchers used descriptive qualitative research, with a focus on research on the role of the Jurug Village Government, The data analysis technique uses an interactive model consisting of data collection, data reduction, and data presentation. The results of research conducted by researchers, the Government has collaborated with the University of Muhammadiyah Ponorogo related to the development of Tourism Villages in Jurug Village. However, in developing and empowering the community in the Tourism Village Program it is still lacking. Many people are still apathetic to the program run by the Jurug Village Government so that the Tourism Village program cannot run properly. In addition, there are problems related to animal waste that pollutes the river that flows through the Pletuk Waterfall tourist site.